Effectiveness of Antenatal Corticosteroids in reducing morbidities and mortality in Preterm neonates: Evidence from a Tertiary Level Hospital in Nepal - Prajwal Paudel; Shree Prasad Adhikari; Kalpana Upadhyaya Subedi; Shailendra Bir Karmacharya; Sandesh Poudel; Megha Mishra; Laxmiswori Prajapati; Lov Sah; Needa Shrestha; Subash Bhattarai; Pratiksha Bhattarai; Avinash K. Sunny (PLoS ONE, 2025)
Background The use of antenatal corticosteroids (ACS) in mothers less than 34 weeks’ period of gestation has shown promising results with significant reduction in neonatal mortality and morbidities in high income settings. This study was carried out to assess the effectiveness of ACS in terms of neonatal outcome in less than 34 weeks in resource limited settings. Methods A prospective study was conducted from 15 March 2022 to 14 March 2023 among the babies born before 34 weeks’ period of gestation (POG), in Paropakar maternity hospital, Nepal. Descriptive statistics using frequency and percentages was used to describe the socio-demographic, obstetric and neonatal characteristics. Multi-variable logistic regression analysis was done to assess the significance of ACS against various neonatal conditions. Results Out of 358 preterm neonates (<34 weeks), 206 were born to mothers who received ACS and 152 to mothers who did not. Mothers having any complications during delivery were more likely to receive ACS, (69.7% vs 50.0%, p = 0.002). Newborns of mothers who received ACS had significantly lower rates of respiratory distress syndrome (21.8% vs 61.8%, p < 0.001), necrotizing enterocolitis (5.8% vs 19.7%, p < 0.001), perinatal asphyxia (18.4% vs 35.5%, p < 0.001), neonatal sepsis (32.0% vs 43.4%, p < 0.027), and need for mechanical ventilation (15.5% vs 41.4%, p < 0.001). Newborn of mothers who did not receive ACS had higher odds of respiratory distress syndrome (adjusted odds ratio (a0R): 4.181, 95% CI: 2.462–7.100) and the need for mechanical ventilation (a0R: 2.266, 95% CI: 1.300–3.950). Lack of exposure to ACS was associated with higher odds of prolonged hospital stay (aOR: 3.321, 95% CI: 1.957–5.638) and mortality (aOR: 5.731, 95% CI: 3.199–10.266). Conclusion ACS was more frequently used in mothers of less than 34 weeks POG having some complications during pregnancy. Use of ACS in deliveries of less than 34 weeks POG was associated with reduced risk of RDS, NEC and need for Mechanical Ventilation along with decrease hospital stay and neonatal mortality. Strengthening national guidelines with recommendation for the use of ACS in mothers less than 34 weeks POG can avert deaths due to complications of prematurity and help save more newborns.